A Bitter-Sweet Story: Unraveling the Genes Involved in Quinolizidine Alkaloid Synthesis in Lupinus albus - Osorio, Claudia E.; Till, Bradley J. (Frontiers in Plant Science, 2022)
Alkaloids are part of a structurally diverse group of over 21,000 cyclic nitrogen-containing secondary metabolites that are found in over 20% of plant species. Lupinus albus are naturally containing quinolizidine alkaloid (QA) legumes, with wild accessions containing up to 11% of QA in seeds. Notwithstanding their clear advantages as a natural protecting system, lupin-breeding programs have selected against QA content a without proper understanding of quinolizidione alkaloid biosynthetic pathway. This review summarizes the current status in this field, with focus on the utilization of natural mutations such as the one contained in pauper locus, and more recently the development of molecular markers, which along with the advent of sequencing technology, have facilitated the identification of candidate genes located in the pauper region. New insights for future research are provided, including the utilization of differentially expressed genes located on the pauper locus, as candidates for genome editing.Identification of the main genes involved in the biosynthesis of QA will enable precision breeding of low-alkaloid, high nutrition white lupin. This is important as plant based high quality protein for food and feed is an essential for sustainable agricultural productivity.